In heart failure, echocardiographic parameters of right ventricular function are powerful tools to predict renal failure - Reinecke, Alexander; Dißmann, Paulina; Frey, Norbert; Müller, Oliver J.; Seoudy, Hatim; Frank, Johanne; Frank, Derk; Spehlmann, Martina-Elisabeth (ESC heart failure, 2025)
Background Chronic kidney disease (CKD) has a high prevalence in patients with heart failure (HF) and is associated with prolonged hospitalization, increased need for intensive care and mortality. There is an urgent need to identify factors that influence the interaction between heart and kidney disorders, often described as cardiorenal syndrome (CRS). We investigated the epidemiology and risk factors of renal insufficiency in patients with HF. Methods We conducted a retrospective cohort study including 281 consecutive patients with HF that are examined at regular intervals at our outpatient clinic for HF. CKD was defined as the presence of an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2 and worsening renal function (WRF) was defined as a decrease of eGFR > 15% within a year. We assessed the patient's medical history, laboratory and echocardiographic parameters at baseline and after 12 months. Results Right ventricular dysfunction was associated with CKD and WRF. In particular, echocardiographic parameters ‘tricuspid annular plane systolic excursion (TAPSE) < 15 mm’ (P < 0.001; OR 2.932), ‘tricuspid regurgitation (TR) > I°’ [P < 0.001; odds ratio (OR) 5.958] and dilatation of inferior vena cava (IVC) (P < 0.001; OR 3.670) were significantly correlated with renal failure. N-terminal pro-B-type natriuretic peptide levels were significantly associated with CKD (P < 0.001; OR 6.109) and correlated with pressure and volume load of the right heart. Conclusions The results of this work support the theory of right-sided cardiac backward failure, often accompanied by hypervolaemia, as a leading cause of HF-related renal failure. Right heart parameters, especially TR, TAPSE and IVC, are obtained easily by transthoracic echocardiography and can predict renal failure.
Online veröffentlicht am 25. Februar 2025
Gesehen am 26.08.2025